Emerging concepts of miRNA therapeutics: from cells to clinic - Diener, Caroline; Keller, Andreas; Meese, Eckart (Trends in genetics, 2022)
MicroRNAs (miRNAs) are very powerful genetic regulators, as evidenced by the fact that a single miRNA can direct entire cellular pathways via interacting with a broad spectrum of target genes. This property renders miRNAs as highly interesting therapeutic tools to restore cell functions that are altered as part of a disease phenotype. However, this strength of miRNAs is also a weakness because their cellular effects are so numerous that off-target effects can hardly be avoided. In this review, we point out the main challenges and the strategies to specifically address the problems that need to be surmounted in the push toward a therapeutic application of miRNAs. Particular emphasis is given to approaches that have already found their way into clinical studies. Single microRNAs (miRNAs) regulate large subsets of mRNA targets. Although this property makes miRNAs potentially a powerful therapeutic tool, it also represents a major challenge in terms of controlling adverse effects that have been observed in clinical trials.Besides systemic applications via injection and infusion, advanced strategies emerge for miRNA-based drug administration via implantable 3D matrices, inhalation schemes, and intake via food.A combination of miRNA therapeutics with chemical modifications, biomolecule conjugation, or the use of carriers improves a site-directed and efficient cell targeting.A comprehensive risk assessment of miRNA therapeutics is required before any in vivo targeting to minimize off-target effects and to avoid overdosing of miRNAs.